Renal transplant anastomotic time–Every minute counts! - Mahajan, Nikhil; Heer, Munish K.; Trevillian, Paul R. (Frontiers in Medicine, 2023)
The impact of Anastomotic time in renal transplant is under recognized and not well studied. It is one of the few controllable factors that affects the incidence of delayed graft function (DGF). Our study aimed at quantifying the impact of anastomotic time. We performed retrospective review of 424 Renal transplants between the year 2006 and 2020. 247 deceased donor renal transplant formed the study cohort. Patients were divided into two groups based on presence or absence of DGF. Variables with p<0.3 were analysed using the Binary logistic regression test. The final analysis showed Anastomotic time to be significantly associated with DGF with odds ratio of 1.04 per minute corresponding to 4% increase in DGF incidence with every minute increment in anastomotic time. Other variables that had significant impact on DGF were DCD donor (odds ratio - 8.7) and donor terminal creatinine. We concluded that anastomotic time had significant impact on the development of DGF and hence should be minimised.